Sho‘ba nomi: VPN (Virtual Private Network) Yordamida Korporativ Tarmoq Xavfsizligini Ta’minlash - Raxmonqulov Diyorjon Ulug’bek o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores and analyzes technologies for ensuring corporate network security using VPN (Virtual Private Network). The main VPN protocols, their advantages, and disadvantages are examined to highlight the role and prospects of this technology in safeguarding data.